"You're on mute!" Does pediatric CF home spirometry require physiologist supervision?. Issue 1 (1st October 2021) - Fettes, Emma; Riley, Mollie; Brotherston, Stephanie; Doughty, Claire; Griffiths, Benjamin; Laverty, Aidan; Aurora, Paul
Abstract: Introduction: The coronavirus disease 2019 (COVID‐19) pandemic has accelerated the move towards home spirometry monitoring, including in children. The aim of this study is to determine whether the remote supervision of spirometry by a physiologist improves the technical quality and failure rate of the maneuvers. Method: Children with cystic fibrosis who had been provided with NuvoAir home spirometers were randomly allocated to either supervised or unsupervised home spirometry following a detailed training session. Home spirometry was performed every 2 weeks for 12 weeks. Tests were assigned a quality factor (QF) using our laboratory grading system as per American Thoracic Society/European Respiratory Society standards, with tests marked from A to D, or Fail. In our laboratory, we aim for QF A in all spirometry tests, but report results of QF B or C with a cautionary note. QF A was, therefore, the primary outcome, and QF A–C, the secondary outcome. Results: Sixty‐one patients were enrolled; 166 measurements were obtained in the supervised group, and 153 in the unsupervised group. Significantly more measurements achieved QF A in the supervised compared to unsupervised group (89% vs. 74%; p  = <0.001), while proportions reaching Grade A–C were similar (99% vs. 95%; p  = 0.1). All significant declines in spirometry results had a clinical rather than technical reason. Family/patient feedback for both arms was very positive. Conclusion: These results suggest that home spirometry in children should ideally be remotely supervised by a physiologist, but acceptable results can be obtained if resources do not allow this, provided that training is delivered and results monitored according to our protocol.